Two new species of Epirhyssa (Hymenoptera: Ichneumonidae: Rhyssinae) from Costa Rica - Zuñiga, Ronald; Hanson, Paul (Zootaxa, 2024)
As a result of continuing research on the ichneumonid wasps of Costa Rica, two new species of Epirhyssa (Rhyssinae) are described: E. leonoreae and E. lewisi. A key is provided for the identification of all 14 species now known to occur in the country.